2020
DOI: 10.1002/iub.2259
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of miRNAs as a signature for diagnosis and prognosis of gastric cancer and their involvement in the mechanism underlying gastric carcinogenesis and progression

Abstract: Gastric cancer (GC) is the second main cause of cancer‐related mortality worldwide. The poor prognosis and survival of GC are due to diagnosis in an advanced, noncurable stage and with a restricted response to chemotherapy. GC is usually monitored in an advanced stage; therefore, the poor prognosis and lower level of survival rate with a restricted response to chemotherapy can be detected. Valuable and sensible biomarkers are urgently needed to display screen patients with a high risk of GC that can complement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 175 publications
0
7
0
Order By: Relevance
“…A limited number of biomarker signatures are available and their diagnostic accuracy remains inadequate for diagnosing patients with gastric cancer [ 33 ]. Using the detection of miRNAs as the valuable and sensible biomarkers are urgently needed for gastric patients, thus complementing endoscopic diagnosis [ 34 ]. A retrospective study demonstrated a predictive value of some miRNAs including miR-221, miR-224, miR-520, and miR-375 for a therapeutic effect of chemotherapy based on platinum derivates in gastric cancer [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…A limited number of biomarker signatures are available and their diagnostic accuracy remains inadequate for diagnosing patients with gastric cancer [ 33 ]. Using the detection of miRNAs as the valuable and sensible biomarkers are urgently needed for gastric patients, thus complementing endoscopic diagnosis [ 34 ]. A retrospective study demonstrated a predictive value of some miRNAs including miR-221, miR-224, miR-520, and miR-375 for a therapeutic effect of chemotherapy based on platinum derivates in gastric cancer [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, miRNAs are thought to link with various biological and pathological events including invasion, migration, cell proliferation, angiogenesis, metastasis, and apoptosis (Abolghasemi et al, 2020a; Pereira et al, 2020; Wu et al, 2020; You et al, 2020). It has been found that dysregulation of miRNAs can be associated with tumorigenesis and different aspects of cancer progression, especially GC (Ahadi, 2020; Streleckiene et al, 2020), which is considered as a heterogeneous disorder that results in cancer‐related deaths worldwide. It has been recently revealed that miRNAs are one of the novel mediators involved in pathogenesis and development of GC and GC‐related disease.…”
Section: Novel Insights Into the Correlation Between Mirnas With Gcmentioning
confidence: 99%
“…Otherwise, chemotherapy and targeted therapy resistance are challenging in GC. Several miRNAs have been implicated in multidrug resistance (MDR) ( 78 ). Moreover, it has been shown that vitamin D can potentiate the effects of chemotherapy and contribute to overcome the molecular mechanisms of drug resistance ( 79 ).…”
Section: Prognostic and Potential Therapeutic Role Of Mirnas In Gcmentioning
confidence: 99%